1995
DOI: 10.1074/jbc.270.14.7968
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Biochemical Evidence for the Involvement of the Asp-333–His-523 Pair in the Catalytic Mechanism of Soluble Epoxide Hydrolase

Abstract: In order to investigate the involvement of amino acids in the catalytic mechanism of the soluble epoxide hydrolase, different mutants of the murine enzyme were produced using the baculovirus expression system. Our results are consistent with the involvement of Asp-333 and His-523 in a catalytic mechanism similar to that of other alpha/beta hydrolase fold enzymes. Mutation of His-263 to asparagine led to the loss of approximately half the specific activity compared to wild-type enzyme. When His-332 was replaced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
68
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 31 publications
4
68
0
Order By: Relevance
“…The alignment characterization also lead to identification of a proposed catalytic triad of amino acids within sEH. Mutagenesis experiments implicated Asp 333 and His 523 in the catalytic mechanism for sEH, similar to other a/b hydrolase enzymes [67]. The results of the latter investigation indicated that since His 523 was conserved in all epoxide hydrolase across species, and mutation of His 523 in murine sEH resulted in activity of 0.1% of wild-type activity, this residue was likely a key participant in the catalytic mechanism for the hydrolase.…”
Section: Mechanism Of Action/enzymatic Mechanismmentioning
confidence: 58%
“…The alignment characterization also lead to identification of a proposed catalytic triad of amino acids within sEH. Mutagenesis experiments implicated Asp 333 and His 523 in the catalytic mechanism for sEH, similar to other a/b hydrolase enzymes [67]. The results of the latter investigation indicated that since His 523 was conserved in all epoxide hydrolase across species, and mutation of His 523 in murine sEH resulted in activity of 0.1% of wild-type activity, this residue was likely a key participant in the catalytic mechanism for the hydrolase.…”
Section: Mechanism Of Action/enzymatic Mechanismmentioning
confidence: 58%
“…A suggested physiological role of the plant enzymes is through their involvement in the epoxide fatty acid metabolism and biosynthetic pathway of cutin [9]. The reaction mechanism of epoxide hydrolases from mammalian [10][11][12] and bacterial [13,14] sources have been thoroughly investigated through mutagenesis studies, kinetic analyses and solved threedimensional structures of enzyme representatives from mouse [15], human [16], Agrobacterium radiobacter AD1 [17] and Aspergillus niger [18] (see [19] for a recent review). The canonical epoxide hydrolases belong to the structural class of α/β hydrolase fold enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical considerations and experimental data suggest that the enzymatic hydrolysis of epoxides proceeds via intermediate formation of a covalent bond between enzyme and substrate. While the complete catalytic triad of soluble EH has been resolved (Arand et al, 1996;Pinot et al, 1995), only the water-activating histidine of the microsomal EH has been experimentally identified (Bell and Kasper, 1993). In an elegant study, Lacourciere and Armstrong (1993) demonstrated transfer of ''0 from microsomal EH to its substrate l,l0-phenanthroline 5,6-oxide under single-turnover conditions with a stoichiometry that is best explained by the formation of the postulated enzyme-substrate ester.…”
Section: Discussionmentioning
confidence: 99%